Development of a social and professional stress scale for parents of children with autism spectrum disorder - Roberta Fernandes, Yasmin; Anjos, Adilson dos; Giolo, Suely Ruiz; Taisa Padilha Mayer, Nathalia (Brazilian Journal of Biometrics, 2023)
Parents of children with Autism Spectrum Disorder (ASD) may experience increased stress in their social and professional activities due to the challenges of raising a child with ASD. The present study developed a scale to measure the Social and Professional Stress (SPS) experienced daily by these parents. The study sample consisted of 255 parents residing in Brazil aged between 21 and 61 years (mean = 38, SD = 6.0). Item Response Theory (IRT) was used to develop the SPS-Scale, which showed good psychometric properties. Our findings indicated a higher level of SPS among mothers who are primary caregivers and who have children with symptoms of ASD at medium or severe levels. The child's age and the interviewee's marital status also showed an association with the SPS experienced by the parents. Overall, the SPS-Scale proved to be a valid instrument to measure the SPS experienced daily by parents of children or adolescents diagnosed with ASD.